Drying kinetics and quality of instant lime powder processed by foam-mat drying - P. Ritnuch (2018)
Lime juice with sugar, salt and honey added was foamed by addition of two types of foaming agents, glyceryl monostearate (15%) and egg albumin (10.5%). The mixtures containing glyceryl monostearate and egg albumin subsequently were whipped for 20 and 30 min., respectively. The foam was spread on a tray 0.5 cm thick and dried at 60°C, with 0.3 m/s air velocity in a tray dryer. The drying kinetics was modeled using well-known mathematic expressions and the best equation was evaluated. In addition, the qualities of the final product in terms of color (L, a, b), vitamin C, citric acid, pH, total soluble solids, density, dispersibility and viscosity were investigated. The Henderson and Pabis and two-term exponential model were found to be the best model for describing the drying characteristics of instant lime powder at temperatures of 60°C. Statistical analysis of these qualities between the two products showed that there was no significant difference (P > 0.05) in citric acid and vitamin C. However, analysis of colour (L, a, b), dispersibility, viscosity, density, total soluble solid and pH showed a significant difference (P≤0.05). © ISHS.